Quantification of fungal abundance on cultural heritage using real time PCR targeting the β-actin gene - Ettenauer, Jörg; Piñar, Guadalupe; Tafer, Hakim; Sterflinger, Katja (Frontiers in Microbiology, 2014)
The traditional methodology used for the identification of microbes colonizing our cultural heritage was the application of cultivation methods and/or microscopy. This approach has many advantages, as living microorganisms may be obtained for physiological investigations. In addition, these techniques allow the quantitative and qualitative assessment of the investigated environment. Quantitative analyses are done by plate count and the determination of abundance by the colony forming unit (CFU). Nevertheless, these techniques have many drawbacks that lead to an underestimation of the cell numbers and do not provide a comprehensive overview of the composition of the inhabiting microbiota. In the last decades, several molecular techniques have been developed enabling many advantages over the cultivation approach. Mainly PCR-based, fingerprinting techniques allow a qualitative detection and identification of the microbiota. In this study, we developed a real time PCR method as a simple, rapid and reliable tool to detect and quantify fungal abundance using the β-actin gene, which is known to appear as a single-copy gene in fungi. To this end, five different indoor thermal insulation materials applied for historical buildings that were previously tested for their bio-susceptibility against various fungi were subjected to qPCR analyses. The obtained results were compared with those obtained from a previous study investigating the bio-susceptibility of the insulation materials using classical cultivation experiments. Both results correlated well, revealing that Perlite plaster was the most suitable insulation material, showing the lowest fungal CFU and qPCR values. In contrast, insulations made of wood showed to be not recommendable from the microbiological point of view. In addition, the potential of qPCR was tested in other materials of cultural heritage, as old parchments, showing to be a suitable method for measuring fungal abundance in these delicate materials.